THE POSITION OF CHINA’S FOREIGN DIRECT INVESTMENTS IN THE GLOBAL ECONOMY AND THE BARRIERS TO THE BELT-ROAD INITIATIVE (Third Sector Social Economic Review, 2020)
The study aims to shed light on the past and future position of the Chinese economy, which has increased its influence in global trade and capital in the last 30 years and its growing production, technology dynamics. This Asian country, which has become a driving force in the world economy in global trade and capital markets, has begun to compete with the developed industrial countries, which are known as the driving and hegemonic power, in the last century. It is assumed that this competition will accelerate not only in the field of economy but also in global political politics and will pave the way for new political polarizations. The study aims to establish connections on China's increasing role in political politics while becoming an undeniable commercial power. With the information links at the beginning of the introduction, the infrastructure factors that led China to a great leap after 1980 will be revealed, and the capacity of today's Chinese economy to direct the global capital and trade system will be questioned within the framework of its advantages and disadvantages. After that, possible factors that will affect the country's ability to attract direct investments, the process of becoming a global net investor and its continuity will be examined. In the last section, there is also a summary area of study on the main objectives of the Belt and Road Project, which is of great importance for the continuity of the Chinese government's post-2013 global investor position, its advantages, and the internal and external problems it will face during its implementation. With this summary study area, China's global investor position on alternative routes, future targets and possible obstacles will be examined within the framework of global trade-finance markets.
Keywords: China’s Economy; Global Trade - Financial System Integration; Outward Foreign Direct Investments; Belt-Road Initiative